High-altitude pulmonary edema is aggravated by risk loci and associated transcription factors in HIF-prolyl hydroxylases. Issue 18 (18th May 2021) - Sharma, Kavita; Mishra, Aastha; Singh, Himanshu N; Parashar, Deepak; Alam, Perwez; Thinlas, Tashi; Mohammad, Ghulam; Kukreti, Ritushree; Syed, Mansoor Ali; Pasha, M A Qadar
Abstract: High-altitude (HA, >2500 m) hypoxic exposure evokes several physiological processes that may be abetted by differential genetic distribution in sojourners, who are susceptible to various HA disorders, such as high-altitude pulmonary edema (HAPE). The genetic variants in hypoxia-sensing genes influence the transcriptional output; however the functional role has not been investigated in HAPE. This study explored the two hypoxia- sensing genes, prolyl hydroxylase domain protein 2 ( EGLN1 ) and factor inhibiting HIF-1α ( HIF1AN ) in HA adaptation and maladaptation in three well-characterized groups: highland natives, HAPE-free controls and HAPE-patients. The two genes were sequenced and subsequently validated through genotyping of significant single nucleotide polymorphisms (SNPs), haplotyping and multifactor dimensionality reduction. Three EGLN1 SNPs rs1538664, rs479200 and rs480902 and their haplotypes emerged significant in HAPE. Blood gene expression and protein levels also differed significantly ( P  < 0.05) and correlated with clinical parameters and respective alleles. The RegulomeDB annotation exercises of the loci corroborated regulatory role. Allele-specific differential expression was evidenced by luciferase assay followed by electrophoretic mobility shift assay, liquid chromatography with tandem mass spectrometry and supershift assays, which confirmed allele-specific transcription factor (TF) binding of FUS RNA-binding protein (FUS) with rs1538664A, Rho GDP dissociation inhibitor 1 (ARHDGIA) with rs479200T and hypoxia upregulated protein 1 (HYOU1) with rs480902C. Docking simulation studies were in sync for the DNA-TF structural variations. There was strong networking among the TFs that revealed physiological consequences through relevant pathways. The two hydroxylases appear crucial in the regulation of hypoxia-inducible responses.